2007
DOI: 10.1002/cvde.200606532
|View full text |Cite
|
Sign up to set email alerts
|

CVD‐Fabricated Aluminum Oxide Coatings from Aluminum tri‐iso‐propoxide: Correlation Between Processing Conditions and Composition

Abstract: This paper presents results on aluminum oxide thin films processed using metal-organic (MO) CVD from aluminum tri-isopropoxide (ATI) without any additional oxygen source, in the temperature range 623-973 K. The films do not diffract X-rays, except when grown at 973 K or annealed at 1073 K. Their composition was investigated using several techniques; electron probe micro analysis (EPMA), energy dispersive X-ray spectroscopy (EDX), elastic recoil detection analysis (ERDA), and Rutherford back-scattering spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 54 publications
2
65
0
Order By: Relevance
“…Silicon substrates (10 × 10 mm) cut from 4″ Si (001) wafers (Sil'tronix-ST), placed at intermediate positions, were also coated and used for TEM analysis. We have already demonstrated that the characteristics of aAl 2 O 3 films are independent of the nature of the substrate, namely AISI 304 L stainless steel (SS), (100) oriented Si wafers, and thermally grown silica on Si wafers [13]. All samples were cleaned in an ultrasonic bath with acetone and ethanol, and were immediately introduced to the reactor.…”
Section: Thin Film Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon substrates (10 × 10 mm) cut from 4″ Si (001) wafers (Sil'tronix-ST), placed at intermediate positions, were also coated and used for TEM analysis. We have already demonstrated that the characteristics of aAl 2 O 3 films are independent of the nature of the substrate, namely AISI 304 L stainless steel (SS), (100) oriented Si wafers, and thermally grown silica on Si wafers [13]. All samples were cleaned in an ultrasonic bath with acetone and ethanol, and were immediately introduced to the reactor.…”
Section: Thin Film Depositionmentioning
confidence: 99%
“…The authors group has developed various chemical vapor deposition, CVD processes for the production of amorphous alumina, a-Al 2 O 3 films [13][14][15]. Such films, processed from aluminum tri-isopropoxide, ATI contain a large percentage of penta-coordinated Al 3+ ions, as was demonstrated by 27 Al nuclear magnetic resonance, NMR spectroscopy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Significant work has been provided by the authors in the recent years in this field. Especially, the relation between the operating conditions of Metalorganic Chemical Vapor Deposition (MOCVD) and the characteristics of the obtained amorphous Al 2 O 3 coatings, including the modeling of the process considering appropriate chemical kinetic schemes [1][2][3][4][5][6] was discussed. The rationale of these investigations is based on two pillars: the first concerns the moderate deposition temperature which is compatible with the thermal loads the substrate can tolerate without modification of its microstructure and, consequently of its properties and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Gleizes et al measured similar O/Al atomic ratio (EPMA) for alumina coatings deposited by MOCVD with vaporized ATI in the temperature range of 480-600 °C. [ 15 ] The evolution of the elemental composition with deposition temperature observed by EPMA was further investigated using XPS (Figure 2 b). The amount of aliphatic carbon (C-C and C-H bonds only) is less than 1 at% and likely results from small amounts of solvent residue incorporated in the coating during growth.…”
Section: Composition and Morphology Of Amorphous Alumina Coatingsmentioning
confidence: 99%
“…[ 7,8,[11][12][13][14][15][16] ATI yields amorphous and stoichiometric alumina coatings with a smooth and dense microstructure at 5 Torr in the temperature range 420 to 650 °C. [ 7,8,14,15 ] Higher process temperatures lead to the deposition of nanocrystallized γ -Al 2 O 3 [ 15 ] or to the homogeneous decomposition of ATI, which generates a different microstructure. [ 11 ] The ATI molecule is well described in the literature.…”
mentioning
confidence: 99%